Greek and Latin Music Theory : Principles and Challenges - Nowacki, Edward; Nowacki, Edward (Book collections on Project MUSE., 2020)
A long-needed overview of, and guide to, the principles behind the treatises on music theory written in ancient Greece and Rome and continuing through the Middle Ages.